School-based intervention combining nutrition education and provision of healthy foods to increase fruit and vegetable consumption in Viet Nam - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The intervention was designed and tested in 12 schools in peri-urban Viet Nam. The results were published in 2021. The intervention was co-developed by A4NH and the National Institute of Nutrition (NIN) under the umbrella of the National Strategy on Nutrition. It is poised to easily go to scale.